ANNUAL MOISTURE BALANCE REGIME IN ZONAL TYPES OF LANDSCAPES OF THE ROSTOV REGION (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Based on the analysis of the long-term dynamics of annual and seasonal values of the main meteorological characteristics for 36 weather stations, the values of the moisture balance for warm, cold periods and for the year were established both in the Rostov Region as a whole and in zonal landscapes. There is a clearly defined annual course of the moisture balance. A positive moisture balance is observed in winter for all weather stations in the region and in all zonal landscapes, and the maximum disadvantage is in summer.
Keywords: moisture balance; zonal landscapes; annual course of moisture balance; Rostov Region